A rare case report of Sandoff disease presented as neuroregression disorder - Sharja Phuljhele; Yogita Rathi (Pediatric Review: International Journal of Pediatric Research, 2019)
Sandhoff disease is a rare lysosomal storage disorder which is inherited in an autosomal recessive pattern. The prevalence of the disease is 1 in 384000 live births. Here the present case report of 14 month old male child who was presented with macrocephaly, regression of developmental milestones and seizures. Fundus examination showed macular cherry red spot. Enzyme studies revealed reduced levels of beta hexosaminidase A and B, following which a diagnosis of Sandhoff disease was made. Fundus examination showed macular cherry red spot. Mother was offered prenatal diagnosis of the fetus in the subsequent pregnancy, which was also found to have the same enzyme deficiency and the pregnancy was medically terminated. Early identification of this neurodegenerative disorder, helped in preventing the birth of subsequent affected children in the same family, thereby reducing the burden on the family as well as the society.